PERANCANGAN DAN PEMBUATAN APLIKASI INVENTORY MANAGEMENT BERBASIS WEB PADA PT. X MENGGUNAKAN METODE EOQ(Economic Order Quantity) - Reza Ghaudi Farhad; Ery Dewayani; Manatap Dolok Lauro (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Inventory is an activity that includes goods owned by a company with the intention of being sold within a certain business period, or inventories of goods that are still in construction or production processes, or inventories of raw materials awaiting use in a production process. PT. X is a company whose scope of business includes the distribution of communication equipment, accessories, electronic devices. PT. X itself sells several kinds of electronic products such as printers, cellphones, barcode scanners, computers, and others. Currently PT.X is carrying out data management of PT. X still enters data manually into Microsoft Excel, even reporting data for bookkeeping is still done manually. So it is very ineffective and data can be easily manipulated and if an error occurs in the storage on the device or the device is suddenly damaged, the data that has been collected can be lost. Web-based Inventory Management application at PT. X which will be made later aims to be a system that will assist in recording incoming and outgoing stock of goods. The process of making applications that are made using the waterfall method, with object-oriented design methods using the UML method, and the framework used uses the Laravel PHP framework.